Kontinuität im Neubeginn. Reden der Zentralen Veranstaltung der Universität Hamburg am 6. November 2015 anlässlich des 70. Jahrestags ihrer Wiedereröffnung 1945 - Fegebank, Katharina (Hamburger Universitätsreden Neue Folge, 2016)
After the occupation of Hamburg by British troops on May 3rd, 1945, the Hamburg University was closed, but reopened on November 6th, 1945 - half a year after the end of the "Third Reich" and the Second World War. On the occasion of the 70th anniversary of this reopening on 6 November 2015, the University of Hamburg took the opportunity to publicly discuss the difficult transition of its own institution from the Nazi dictatorship into the democratic post-war period. This volume of "Hamburger Universitätsreden" documents the four speeches held on on this occation.